An Analysis of Figurative Language Used in Fashion and Beauty Advertisements of Red Digital Magazine - Anastari, Indra; Agustina, Hiqma Nur; Suharto, Ririn Pratiwi (Universitas Muhammadiyah Gorontalo, 2024)
This study aims to analyze the figurative language used in fashion and beauty advertisements of Red Digital Magazine. There were two purposes of this research: (1) to identify the types of figurative language used in fashion and beauty advertisements of Red Digital Magazine and (2) to describe the meaning of the figurative language used in fashion and beauty advertisements of Red Digital Magazine. The data source of this research was advertisements from 12 Red Digital Magazine, 15 fashion advertisements, and 12 beauty advertisements published in 2022. The data of this research were sentences written in the texts of the advertisements. These data were analyzed by using the qualitative method. This research collects, analyzes, and interprets data through data collection techniques such as observation, documentation, and questionnaires. Based on Johnson & Arp's (2017) theory, it is shown that there were 7 types of figurative language. Starting from the most frequently occurring, they were overstatement/hyperbole, metaphor, personification, simile, paradox, metonymy, and allegory. Overstatement/hyperbole was the most commonly found in advertisements among those types of figurative language. The use of this type can give an impression and influence to the readers; therefore, it is often used to describe the exaggerated quality of the product. Furthermore, the use of figurative language is one way to improve writing in advertising, using figures of speech can make the memorability of advertising sentences, creates imagination, makes sentences more meaningful, and most importantly increases the interest of the reader.